Seeing like an Inuit family: The relationship between house form and culture in northern Canada - Dawson, Peter (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2006)
AbstractIn his classic essay Seasonal Variations of the Eskimo, Marcel Mauss argued that a strong relationship exists between the spatial organisation of traditional Inuit house forms and the social morphology of the families they shelter. These observations anticipate later works in anthropology that examine how cultural processes are reflected in, and sustained by, the built environment. Such ideas are important when considering the effects of post-war housing programs on Inuit families in the Canadian Arctic. During the 1960s, attempts were made to restructure the routines of Inuit families through Euro-Canadian architecture and home economics classes. Recent ethnographic observations of Inuit households in operation, however, reveal that many continue to use their houses in traditional ways. By doing so, Inuit families are attempting to adapt to dwellings designed around another culture’s concept of homemaking and family life. Mauss’s ideas are therefore a poignant reminder of the need to take cultural factors into account when developing aboriginal housing policy.